Conservation Easement Enabling Statutes: Perspectives on Reform (Utah Environmental Law Review; Vol 33 No 1 (2013), 2014)
By now, the public has invested billions of dollars in many tens of thousands of conservation easements. With the widespread use of the conservation easement as a land protection tool have come increasingly sophisticated and thorny issues and challenges. This Article focuses on state conservation easement enabling statutes and related reforms. It is presented as an exchange of ideas between the two Authors who come to the table with different backgrounds but a shared commitment to, and understanding of, the importance of land conservation. The goal is to provide food for thought to landowners, land conservation professionals, policymakers, federal and state regulators, and the public when considering possible reforms.